Shotgun proteomic analysis for detecting differentially expressed proteins in the reduced culm number rice - Lee, Joohyun; Jiang, Wenzhu; Qiao, Yongli; Cho, Young-Il; Woo, Mi-Ok; Chin, Joong-Hyun; Kwon, Soon-Wook; Hong, Seong Sig; Choi, Ik-Young; Koh, Hee-Jong (Wiley, 2011)
To survey protein expression patterns in the reduced culm number (RCN) rice, a comparative shotgun proteomic analysis was conducted. For large‐scale protein identification, multidimensional protein identification technology (MudPIT) coupled with pre‐fractionation of plant shoot proteins led to the identification of 3004 non‐redundant rice proteins. By statistically comparing relative amounts of 1353 reproducibly identified proteins between the RCN rice and the wild‐type rice, 44 differentially expressed proteins were detected, where 42 proteins were increased and 2 proteins were decreased in the RCN rice. These proteins appear to have roles in glycolysis, trichloroacetic acid cycle, secondary metabolism, nutrient recycling, and nucleotide metabolism and repair. Consequently, we hypothesized that the RCN rice might fail to maintain sugar nutrient homeostasis. This was confirmed with the observation that the sucrose concentration was increased significantly in the RCN rice compared with the wild‐type rice. Also, the RCN rice showed a hypersensitive response to exogenous sucrose treatment.